MEG Localization in Epilepsy Surgery - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The concordance rate between the anatomical location of interictal magnetoencephalography (MEG) spike foci with the location of ictal onset zones identified by invasive ictal intracranial electroencephalographic (EEG) recordings was determined in 11 children evaluated for epilepsy surgery at the Hospital for Sick Children and University of Toronto, Ontario, Canada.